Migration chez la population indienne de la Baie James: une étude de cas - Piché, Victor (Anthropologica, 2022)
This study attemps to look at the migration behaviour of the Indian population in the James Bay area. The data used here are taken from a demographic survey carried out in 1968 in six villages located around James Bay: Moosonee, Fort Albany, Attawapiskat, Moose Factory, Rupert House and Fort George. Using place of survey and place of last previous residence, it is possible to estimate migration streams from one village to another. The main conclusion is the strong north-south direction of migration.